Jamol SYMBOLS IN MODERN LINGUISTICS: SYMBOLS IN MODERN LINGUISTICS - Rustamov, Ilxom (Журнал иностранных языков и лингвистики, 2022)
The current emphasis on technocracy has placed the study of language in the anthropocentric sphere, focusing not only on linguistic but also non-linguistic characteristics which are a unity of language, individual, culture, cognition, ethnics and spirituality. This linguistic approach considers the human as the measure of all things in the world, since humans perceive the world with their senses, evaluate and analyze through their consciousness, even update existing information in the real world creating language symbols for practical usage in the universe.